Istri Bergaji: Analisis Peran Wanita Bekerja Dalam Meningkatkan Ekonomi Keluarga - Fika Andriana, Agustinar & Dessy Asnita (Hukum Keluarga Islam IAIN LANGSA, 2021)
The Cases in this paper include what are the causes of wives having to work outside as housewives? And what is the position of wives in running as housewives and their position as workers in order to improve the family economy? The purpose of writing this paper is to find out the causes of wives working outside other than as housewives and also as working mothers. This writing uses a qualitative descriptive method. The Information collection method used in this paper is observation, interviews, and data analysis using two data, namely primary and secondary data. The result of this paper indicates that some of the causes of wives having to work outside, among others, are the desire to increase family income, the desire to help husband because the wife’s income tends to below, and apply the knowledge gained during education in the world of work. The role of the wife in this paper looks very influential in improving the family economy. Because a working wife can fill meaningful sectors in the family. These include education, health, economic and social zones. In addition, with the work of the wife, the position of the wife automatically becomes double, namely as a housewife and a working mother.